I'm having trouble solving this problem using the Fitch system. As I understand Fitch, if the goal has the form $(φ \implies ψ)$, it is often good to assume $φ$ and prove $ψ$ and then use Implication Introduction to derive the goal. Since there are no premises, to prove $(p \implies (q \implies r)) \implies ((p \implies q) \implies (p \implies r))$ with the Fitch system, I'll need to assume the antecedent $(p \implies (q \implies r))$ and use Implication introduction to derive the consequent $((p \implies q) \implies (p \implies r))$. I'm stuck though as using Stanford's Fitch system, assuming $(p \implies (q \implies r))$ results in $p(q)$ and assuming $p \implies q \implies r$ results in $p$. How should I think about this problem so I can resolve the proof?

  • $\begingroup$ Of note: part of my problem was using the symbols (p ⇒ (q ⇒ r)) in the Stanford Fitch system engine and not => $\endgroup$ – Mr. Kennedy Apr 24 '17 at 19:13
  • $\begingroup$ When I click on your link I get a "Show Answer" button. Don't you? $\endgroup$ – Pierre-Yves Gaillard Apr 28 '17 at 11:02

1) $p \to (q \to r)$ --- assumed [a]

2) $p \to q$ --- assumed [b]

3) $p$ --- assumed [c]

4) $q$ --- from 3) and 2) by $\to$-elim

5) $q \to r$ --- from 3) and 1) by $\to$-elim

6) $r$ --- from 4) and 5) by $\to$-elmi

7) $p \to r$ --- from 3) and 6) by $\to$-intro, discharging [b]

8) $(p \to q) \to (p \to r)$ --- from 2) and 7) by $\to$-intro, discharging [b]

9) $(p \to (q \to r)) \to [(p \to q) \to (p \to r)]$ --- from 1) and 8) by $\to$-intro, discharging [a].

As you can see, we have to assume all the antecedents of the conditionals involved.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.